An evaluation of stem-based learning activities: Student’s interest and understanding of the force and motion concepts - Maya Insan Mohd Terang (2022)
This study's objective is to assess a number of STEM-based learning activities (STEM-bLA) utilising the Context, Input, Process, and Product (CIPP) model in order to gauge students' conceptual interest in and grasp of the subject of Force and Motion. Researchers used the Analysis, Designing, Development, Implementation, and Evaluation (ADDIE) paradigm of instructional design for creating STEM-bLA. In a typical everyday school in a rural area of Sabah, researchers have looked at the qualities of learning activities that can pique students' interests, particularly among form four secondary physics students. The researcher then developed a series of STEM-bLA on the basis of the identified learning activities with the goal of influencing students' conceptual knowledge of the subject of force and motion. A case study methodology is used in this evaluation research to investigate the genuine context-bound factors as informants, location, and time. This qualitative study was conducted with 17 students in a science stream class in a regular B school in a rural part of Sabah. Data were gathered by observation, discussion in the classroom, student responses to the assigned activities, and use of the STEM-bLA, SM1, SM2, and others. The primary materials for this study were the researcher's field notes and the students' written responses during a three-month period. The transcribed interviews with the informants were triangulated with member and panel experts to confirm the reliability of the data. The information gleaned from participant responses to the diagnostic test and tasks at the conclusion of each STEM-bLA was compared to the data gathered. The outcome demonstrates that this STEM-bLA has increased students' enthusiasm in studying physics. Additionally, there were modifications in the way that students understood physics conceptually. The preceding misunderstanding is successfully corrected. At the same time, a fresh misunderstanding is emerging. This STEM-bLA is used as teaching resources by educational professionals, particularly for certain physics ideas. In addition, this STEM-bLA serves as an "engagement tool" to pique students’ curiosity about what they are learning. Last but not least, this STEM-bLA can be used as a "learning probe" to track how well the physics students are grasping particular physics ideas. However, the study only touched on a few Force and Motion-related physics concepts. In order to help instructors use STEM-bLA in the teaching and learning of physics ideas for the topic of Forces and Motion, a framework was later developed using the qualitative findings. The framework can be effectively used to promote students' HOTS, foster conceptual understanding, and enable meaningful science learning. More STEM-bLA will be created as a result, as indicated for further research. Other subjects and more physics concepts will be covered in the exercises. This work will eventually result in more engaging physics learning exercises for the students and will aid in the improvement of their conceptual knowledge of physics.